2014
DOI: 10.1017/s0950268814001642
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for methicillin-resistant Staphylococcus aureus skin and soft-tissue infections in outpatients in Taiwan

Abstract: Information on the risk factors for community-associated skin and soft-tissue infections (SSTIs) due to methicillin-resistant Staphylococcus aureus in Asian populations is scarce. To this end we performed a case-control study of patients treated at two hospital-affiliated outpatient clinics in Taiwan to determine potential risk factors for MRSA SSTIs. S. aureus was isolated from 39 of 100 eligible patients, and 74% were MRSA. Apart from resistance to clindamycin and erythromycin, most MRSA isolates were suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…In this study it was found that the risk factors for MRSA vs. non-MRSA SSTI in hospitalized patients were the presence of abscess, cellulitis, age of 18-44 years, and previous outpatient antibiotic treatment. Some of the risk factors identified in this study are similar to those reported in other studies performed in the USA, Canada, and Taiwan, in which purulent infections (abscesses and purulent cellulitis) (Moran et al, 2006;Haysom et al, 2018) and previous use of antibiotics were associated with MRSA (Moran et al, 2006;Skiest et al, 2007;Stenstrom et al, 2009;Chou et al, 2015). In the present study, diabetes, intravenous drug use, female sex, HIV infection, and athletic team participation (Hota et al, 2007) were not associated with MRSA SSTI, in contrast to the findings of studies in the USA, Canada, and the Middle East (Stenstrom et al, 2009;Ray et al, 2013a;Al Jalaf et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study it was found that the risk factors for MRSA vs. non-MRSA SSTI in hospitalized patients were the presence of abscess, cellulitis, age of 18-44 years, and previous outpatient antibiotic treatment. Some of the risk factors identified in this study are similar to those reported in other studies performed in the USA, Canada, and Taiwan, in which purulent infections (abscesses and purulent cellulitis) (Moran et al, 2006;Haysom et al, 2018) and previous use of antibiotics were associated with MRSA (Moran et al, 2006;Skiest et al, 2007;Stenstrom et al, 2009;Chou et al, 2015). In the present study, diabetes, intravenous drug use, female sex, HIV infection, and athletic team participation (Hota et al, 2007) were not associated with MRSA SSTI, in contrast to the findings of studies in the USA, Canada, and the Middle East (Stenstrom et al, 2009;Ray et al, 2013a;Al Jalaf et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…In Colombia, it is common for clinicians to prescribe penicillins for SSTIs, specifically amoxicillin, amoxicillinclavulanic acid, and dicloxacillin. This finding is similar to those of studies performed in the Middle East and Asia (Chou et al, 2015;Al Jalaf et al, 2018) and in contrast to the findings of other studies in Europe and the USA (Lipsky et al, 2007;Macía-Rodríguez et al, 2017), where an increase in prescription of antibiotics active against MRSA (Szumowski et al, 2007;Hersh, 2008) was noted in emergency rooms in the last decades (Pallin et al, 2008). A systematic review by Abetz et al reported a frequency of treatment failure of 15-38% in SSTI, and an MRSA infection was implicated in this outcome (Abetz et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It may be also involved in systemic infections [61,62]. The pathogen commonly found in acute and chronic infections of the hearing aid with both children [63,64] and adults [65,66]. reported that the implant-associated infection with S. aureus bacteria is developed in 15 out of 44 patients with prosthetic joints [74].…”
Section: Staphylococcus Aureus Germs Are Often Involved In Local Imentioning
confidence: 99%
“…In the USA, colonization by S. aureus is high among SSTI patients, particularly that of USA300 MRSA [ 2 ]. In Taiwan, the prevalence of MRSA in most of the major hospitals ranged from 53 % to 83 % [ 3 ]; MRSA is a major pathogen related to SSTIs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%